Lightweight thermal insulation castable with high strength and high thermal shock resistance and preparation method thereof

By optimizing the raw material composition and particle size distribution of lightweight thermal insulation castable, a porous structure and ceramic bonding phase are formed, which solves the problem of insufficient thermal shock stability and strength of lightweight thermal insulation castable at high temperatures, and achieves the effects of low thermal conductivity, high strength and high stability.

CN120943655APending Publication Date: 2025-11-14武汉钢铁有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511205116.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-27
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing lightweight thermal insulation castables lack thermal shock stability and strength at high temperatures, leading to increased heat loss and failing to meet the needs of high-temperature industrial applications.

Method used

Using raw materials such as mullite hollow spheres, porous calcium hexaaluminate, fused magnesia, and silicon zirconium sol composite binder, a porous structure and ceramic bonding phase are formed by controlling the particle size and ratio, which enhances thermal shock resistance and strength, and explosion-proof organic fibers are added to improve the stability of the material.

Benefits of technology

The thermal conductivity is reduced to below 0.60 W/(m・K) at 1000℃, the room temperature flexural strength is increased to no less than 9.9MPa, and the strength retention rate after 5 water cooling cycles is increased to no less than 86%, which significantly improves the high temperature stability and strength of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a light thermal-insulation castable with high strength and high thermal shock resistance. The light thermal-insulation castable comprises the following raw materials in percentage by weight: 40-75% of mullite hollow spheres or light mullite porous clinker or a mixture of the mullite hollow spheres and the light mullite porous clinker, 15-40% of porous calcium hexaluminate, 5-10% of activated aluminum oxide, 5-10% of fused magnesite and 6-10% of a silicon-zirconium sol composite binding agent, wherein the granularity of the mullite hollow spheres is greater than 0.1 mm and less than or equal to 8mm; the granularity of the porous calcium hexaluminate is greater than 0.1 mm and less than or equal to 3mm; the preparation method comprises the following steps: preparing a dry blend; preparing slurry; performing molding; and demolding and baking. The heat conductivity coefficient at 1000 DEG C is reduced to less than or equal to 0.60 W / (mK) from the existing 0.7 W / (mK), the normal-temperature breaking strength is improved to be not lower than 9.9 MPa from the existing not higher than 9 MPa, the normal-temperature compressive strength is improved to be not lower than 82 MPa from the existing not higher than 75 MPa, and the strength retention rate after 5 times of water cooling is improved to be not lower than 86% from not higher than 85% in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a thermal insulation castable and its preparation method, specifically to a high-strength, high-thermal-shock-stability lightweight thermal insulation castable and its preparation method. Background Technology

[0002] Lightweight thermal insulation castables are a class of functional refractory materials that combine low bulk density (typically ≤1.5 g / cm³), low thermal conductivity (≤0.8 W / (m・K) at room temperature and ≤1.5 W / (m・K) at 1400℃), good high-temperature stability, and castability. Their applications primarily cover high-temperature industrial sectors such as steel, building materials, chemicals, and power generation. Their characteristics include energy saving, simplified construction, and adaptability to complex structures.

[0003] Currently, in the steel industry, lightweight insulating castables are mainly used for permanent layers and insulation layers in high-temperature equipment. Using lightweight insulating castables improves energy efficiency by reducing heat loss. In existing technologies, the lightweight castables used in this field are mainly corundum-mullite lightweight castables and calcium hexaaluminate castables. While these have some insulation effect, they have shortcomings, primarily because they mostly use cement as a binder, resulting in low hot strength and poor thermal shock stability.

[0004] As retrieved: Chinese Patent Publication No. CN10920582 discloses a steel ladle insulation castable and its application. The document uses mullite, pyroxene, and andalusite as aggregates and clay powder, magnesite fine powder, alumina micro powder, and silica micro powder as matrix to develop a castable suitable for steel ladle insulation. It can be used for the permanent layer of steel ladle, furnace lining and ladle cover, but it does not address the thermal shock resistance of the material.

[0005] A paper titled "The Influence of Pure Calcium Aluminate Cement on the Properties of Corundum-Spinel Castables" was published in the *Bulletin of the Chinese Ceramic Society* (2008, 12(6): 1104-1108). The paper analyzed the density, strength, and phase composition of high-alumina hollow spheres after heat treatment. Lightweight castables were then prepared using high-alumina hollow spheres at mass fractions of 30%, 35%, 40%, and 45%, respectively, as aggregate. The influence of the hollow sphere addition on the properties of the lightweight castables was investigated. The results showed that the density and strength of the lightweight castable samples after drying and heat treatment were optimal when the high-alumina hollow sphere addition was 40%. This paper mainly studied the influence of the hollow sphere addition on the strength of the castables, without addressing the slag resistance and thermal conductivity of the castables.

[0006] Both of the above documents use cement binders. At a high temperature of 1400℃, CaO in cement is prone to react with SiO2, Al2O3 and other substances in aggregates to form low-melting-point phases (such as calcium silicates and calcium aluminates, whose melting points are mostly below 1300℃), which leads to a decrease in the material's refractoriness and high-temperature strength. Summary of the Invention

[0007] The present invention aims to overcome the shortcomings of the existing technology and provide a lightweight thermal insulation castable with high strength and high thermal shock stability, and its preparation method. The castable has a thermal conductivity of ≤0.60 W / (m・K) at 1000℃, a flexural strength of not less than 9.9MPa at room temperature, a compressive strength of not less than 82MPa at room temperature, and a strength retention rate of not less than 86% after 5 water cooling cycles. It is also environmentally friendly.

[0008] Measures to achieve the above objectives: A high-strength, high-thermal-shock-stability lightweight insulating castable, comprising the following raw material composition and weight percentage: 40-75% of mullite hollow spheres (0.1mm < particle size ≤ 8mm), or lightweight porous mullite clinker with the same particle size as the mullite hollow spheres, or a mixture of both in any proportion; 15-40% of porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm); 5-10% of activated alumina (<0.088mm particle size); 5-10% of fused magnesia (<0.088mm particle size); and 6-10% of a silicon-zirconium sol-gel composite binder.

[0009] The key is the addition of explosion-proof organic fibers at a weight percentage of 0.01 to 0.15%.

[0010] The key point is that the explosion-proof organic fiber refers to a composite of one or both of polypropylene fiber and polyethylene fiber.

[0011] The specific characteristics are as follows: in the mullite hollow spheres or lightweight mullite porous clinker with a particle size of 0.1mm < ≤ 8mm, the percentage of each particle size grade in the total weight of the added material is as follows: 3mm < ≤ 8mm accounts for 30~50%, 1mm < ≤ 3mm accounts for 20~40%, and 0.1mm < ≤ 1mm accounts for 30~50%.

[0012] The specific details are as follows: In the porous calcium hexaaluminate with a particle size of 0.1 mm < particle size ≤ 3 mm, the percentage of each particle size grade in the total weight of the porous calcium hexaaluminate is as follows: 1 < particle size ≤ 3 mm accounts for 40~60%, and 0.1 < particle size ≤ 1 mm accounts for 40~60%.

[0013] The silicon-zirconium sol composite binder is composed of tetraethyl orthosilicate, ethanol, deionized water, hydrochloric acid, zirconium oxychloride, nitric acid, and γ-aminopropyltriethoxysilane. It is prepared through processes including the preparation of a silicon sol precursor and a zirconium sol precursor, followed by the dropwise addition of the silicon sol precursor to the zirconium sol precursor. Its pH is between 2.0 and 4.0; the solid content in the composite binder is between 15% and 25%; the Si:Zr ratio in the composite binder is between 1:1 and 3 or between 1 and 3:1; and its color is a pale blue emulsion.

[0014] A method for preparing a lightweight insulating castable with high strength and high thermal shock stability, comprising the following steps: 1) Preparation of dry mix: According to the particle size distribution, first add the set amount of mullite hollow spheres, or lightweight mullite porous clinker with the same particle size as mullite hollow spheres, or a mixture of the two in any proportion, porous calcium hexaaluminate, activated alumina, and fused magnesia, and pour the materials into a forced mixer and dry mix for 1 to 3 minutes to form a dry mix; when explosion-proof organic fibers are added, they are also poured in and mixed together. 2) Preparation of slurry: Add the set amount of silicon-zirconium sol composite binder to the dry mixture at a rate of 0.1-0.5 kg / min, and then stir until the slurry is uniform; 3) Place the slurry into a mold pre-coated with a release agent and vibrate to remove air bubbles until it is compacted; 4) After demolding, bake at 105-115℃ and keep warm at this temperature for no less than 20 hours; When it is necessary to measure the thermal conductivity, heat treatment is performed after baking, with the temperature heated to no higher than 1100℃, and the thermal conductivity is measured at this temperature.

[0015] The role and mechanism of each raw material and main process in this invention The reason this invention adds mullite hollow spheres (0.1mm < particle size ≤ 8mm), or lightweight mullite porous clinker with the same particle size as the mullite hollow spheres, or a mixture of both in any proportion, to the castable, controlling the addition amount to 40-75%, and controlling the particle size to 0.1mm < particle size ≤ 8mm, with the following percentages of each particle size class by weight: 3mm < particle size ≤ 8mm 30-50%, 1mm < particle size ≤ 3mm 20-40%, 0.1mm < particle size ≤ 1mm 30-50%, is because mullite hollow spheres or lightweight mullite porous clinker contain many closed or interconnected pores, and the thermal conductivity of air is much lower than that of solid materials. When added to the castable as aggregate, they create more pores in the overall structure of the castable. During heat transfer, the air in these pores blocks the heat transfer, reducing the efficiency of heat conduction through the solid and thus lowering the overall thermal conductivity.

[0016] The reason for adding porous calcium hexaaluminate (0.1 mm < particle size ≤ 3 mm) to the castable in this invention, and controlling the addition amount to 15-40%, is that calcium hexaaluminate belongs to the hexagonal crystal system. Its crystal structure involves a complex packing of aluminum-oxygen tetrahedra (AlO4) and calcium-oxygen polyhedra (CaO6), resulting in numerous gaps and irregularities in atomic arrangement. This structure leads to frequent phonon scattering during propagation, hindering energy transfer. Therefore, calcium hexaaluminate itself has a low inherent thermal conductivity (approximately 1.0-1.5 W / (m·K) at room temperature). The castable of this invention is designed as a lightweight porous structure, with even higher porosity between calcium hexaaluminate and mullite hollow spheres, resulting in a more tortuous heat transfer path and further increasing thermal resistance.

[0017] The reason for adding fused magnesia powder with a particle size of <0.088mm to the castable and controlling the addition amount to 5-10% is as follows: First, it can react with alumina to generate magnesium aluminum spinel in situ, forming microcracks inside the castable and thus improving the thermal shock resistance of the castable. However, the amount of spinel generated in situ cannot be too much, otherwise it will lead to a decrease in the strength of the castable. Therefore, the fused magnesia powder with a particle size of <0.088mm is controlled at 5-10%. Second, adding magnesia as a coagulant accelerator for the silicon zirconium sol composite binder can accelerate the coagulation of the silicon zirconium sol.

[0018] The reason for adding activated alumina powder with a particle size of <0.088mm to the castable and controlling the addition amount to 5-10% is as follows: First, it works synergistically with silica sol: the hydroxyl groups (-OH) on the surface of activated alumina can undergo a condensation reaction with the SiO2 sol particles of silica sol to form Si-O-Al chemical bonds, which strengthens the gel network structure and improves the strength after dehydration at medium temperature (300-600℃); Second, it reacts with magnesia to generate magnesium aluminum spinel in situ, forming microcracks inside the castable and thus improving the thermal shock resistance of the castable; Third, during high-temperature use or baking, the high reactivity of activated alumina enables it to undergo a solid-phase reaction with other components in the castable (such as SiO2, mullite, etc.) to generate a high-performance high-temperature phase.

[0019] The reason for adding a silicon-zirconium sol composite binder to the castable in this invention, and controlling the addition amount to 6-10%, while controlling the solid content in the silicon-zirconium sol composite binder to 15-25%; and the Si:Zr ratio to 1:1-3 or 1-3:1, is as follows: Firstly, it provides bonding and shaping at room temperature, ensuring construction performance. As an inorganic colloidal binder, the core function of silicon-zirconium sol is to bind lightweight aggregates (mullite hollow spheres, porous calcium hexaaluminate) and fine powders (active Al2O3, magnesia) into a whole through the surface adsorption force of colloidal particles. As moisture evaporates, the colloidal particles gradually aggregate and condense, forming... The continuous SiO2-ZrO2 gel network imparts room temperature strength to the castable, ensuring that the green body does not collapse before baking. Secondly, ceramic bonding is formed at medium and high temperatures, improving structural strength. During baking (100-600℃) and use (>600℃), the silicon-zirconium sol undergoes dehydration, sintering, and chemical reactions, transforming from a gel state into a ceramic bonding phase, thus strengthening the material structure. ZrO2 in the silicon-zirconium sol is a key functional component, complementing the characteristics of the lightweight aggregate in the system. Thirdly, although mullite hollow spheres and porous calcium hexaaluminate are lightweight and have low thermal conductivity, their high-temperature structural stability depends on the support of the bonding phase. The high refractoriness of ZrO2 can improve the overall refractoriness of the material (far exceeding the 1850℃ of mullite), broadening its application in ultra-high temperature environments (such as 1600-1800℃); fourth, ZrO2 has a unique "phase transformation toughening" effect: when the temperature changes abruptly, some ZrO2 undergoes a phase transformation from tetragonal to monoclinic, accompanied by a slight volume expansion (about 3-5%), which can offset the internal thermal stress of the material and reduce crack formation. This is particularly important for lightweight aggregates (high porosity, weak thermal shock resistance), significantly improving the thermal shock cycle resistance of castables; fifth, it improves erosion resistance and wear resistance. ZrO2 is not only resistant to high temperatures, but also has excellent chemical stability and hardness (Mohs hardness 8.5). The ceramic bonding phase formed by the zirconium sol composite binder has high density, which can fill the open pores on the surface of lightweight aggregates, reducing the penetration of corrosive media, while improving the wear resistance of the material at room temperature (avoiding wear caused by the loose structure of lightweight aggregates). Therefore, compared with conventional cement-bonded mullite lightweight castables, the present invention has a lower thermal conductivity and higher strength.

[0020] Compared with the prior art, the present invention reduces the thermal conductivity at 1000℃ from no less than 0.7 W / (m·K) to ≤0.60 W / (m·K), increases the room temperature flexural strength from no more than 9 MPa to no less than 9.9 MPa, increases the room temperature compressive strength from no more than 75 MPa to no less than 82 MPa, and increases the strength retention rate after 5 water cooling cycles from no more than 85% to no less than 86%. Detailed Implementation

[0021] The present invention will now be described in detail: Example 1 A high-strength, high-thermal-shock-stability lightweight insulating castable, comprising the following raw materials and their weight percentages: 67% mullite hollow spheres (0.1mm < particle size ≤ 8mm), with the following particle sizes: 40% (3 < particle size ≤ 8mm), 20% (1 < particle size ≤ 3mm), and 40% (0.1 < particle size ≤ 1mm); 15% porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm), with the following particle sizes: 60% (1 < particle size ≤ 3mm), and 40% (0.1 < particle size ≤ 1mm); 5% activated alumina (particle size < 0.088mm); 5% fused magnesia (particle size < 0.088mm); and 8% silicon-zirconium sol-gel composite binder (silicon:zirconium ratio 3:1, solid content 21%). Preparation steps: 1) Preparation of dry mix: 67% mullite hollow spheres (0.1mm < particle size ≤ 8mm), in which the particle size distribution is: 40% 3 < particle size ≤ 8mm, 20% 1 < particle size ≤ 3mm, and 40% 0.1 < particle size ≤ 1mm; 15% porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm), in which the particle size distribution is: 60% 1 < particle size ≤ 3mm, and 40% 0.1 < particle size ≤ 1mm; 5% activated alumina (particle size < 0.088mm); and 5% fused magnesia (particle size < 0.088mm). Pour the above materials into a forced mixer and dry mix for 1 minute to form a dry mix. 2) Preparation of slurry: Add 8% silicon zirconium sol composite binder to the dry mixture at a rate of 0.15 kg / min and stir until the slurry is uniform; 3) Place the slurry into a mold pre-coated with a release agent and vibrate to remove air bubbles until it is compacted; 4) After demolding, bake at 110℃ and keep at this temperature for 24 hours; then heat to 1000℃ and measure the thermal conductivity at this temperature.

[0022] According to the test results, the thermal conductivity of this embodiment at 1000℃ is 0.59 W / m・K, the flexural strength at room temperature is 10.2MPa, the compressive strength at room temperature is 85.3MPa, and the strength retention rate after 5 water cooling cycles is 87%.

[0023] Example 2 A high-strength, high-thermal-shock-stability lightweight insulating castable, comprising the following raw materials and their weight percentages: 40% mullite hollow spheres (0.1mm < particle size ≤ 8mm), with the following particle sizes: 35% for particles 3 < ≤ 8mm, 35% for particles 1 < ≤ 3mm, and 30% for particles 0.1 < ≤ 1mm; 30% porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm), with the following particle sizes: 50% for particles 1 < ≤ 3mm, and 50% for particles 0.1 < ≤ 1mm; 10% activated alumina (particle size < 0.088mm); 10% fused magnesia (particle size < 0.088mm); and 10% silicon-zirconium sol-gel composite binder (silicon:zirconium ratio 2:1, solid content 25%). Preparation steps: 1) Preparation of dry mix: 40% mullite hollow spheres (0.1mm < particle size ≤ 8mm), with the following particle size distribution: 35% 3 < particle size ≤ 8mm, 35% 1 < particle size ≤ 3mm, and 30% 0.1 < particle size ≤ 1mm; 30% porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm), with the following particle size distribution: 50% 1 < particle size ≤ 3mm, and 50% 0.1 < particle size ≤ 1mm; 10% activated alumina (particle size < 0.088mm); and 10% fused magnesia (particle size < 0.088mm). Pour the above materials into a forced mixer and dry mix for 1.5 minutes to form a dry mix. 2) Preparation of slurry: Add 10% silicon zirconium sol composite binder to the dry mixture at a rate of 0.15 kg / min and stir until the slurry is uniform; 3) Place the slurry into a mold pre-coated with a release agent and vibrate to remove air bubbles until it is compacted; 4) After demolding, bake at 115℃ and keep at this temperature for 20 hours; then heat to 1000℃ and measure the thermal conductivity at this temperature.

[0024] According to the test results, the thermal conductivity of this embodiment at 1000℃ is 0.56 W / (m・K), the flexural strength at room temperature is 9.9MPa, the compressive strength at room temperature is 83.9MPa, and the strength retention rate after 5 water cooling cycles is 86%.

[0025] Example 3 A high-strength, high-thermal-shock-stability lightweight insulating castable, comprising the following raw materials and their weight percentages: 50% lightweight porous mullite clinker (0.1mm < particle size ≤ 8mm), with the following particle sizes: 35% for particles 3 < ≤ 8mm, 35% for particles 1 < ≤ 3mm, and 30% for particles 0.1 < ≤ 1mm; 29% porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm), with the following particle sizes: 45% for particles 1 < ≤ 3mm, and 55% for particles 0.1 < ≤ 1mm; 8% activated alumina powder (particle size < 0.088mm); 7% fused magnesia powder (particle size < 0.088mm); and 6% silicon-zirconium sol-gel composite binder (silicon:zirconium ratio 1:1, solid content 15%). Preparation steps: 1) 50% of lightweight mullite porous clinker with a particle size of 0.1mm < ≤ 8mm, in which the particle size distribution is: 35% < 3mm < 8mm, 35% < 1mm < 3mm, and 30% < 0.1mm < 1mm; 29% of porous calcium hexaaluminate with a particle size of 0.1mm < ≤ 3mm, in which the particle size distribution is: 45% < 1mm < 3mm, and 55% < 0.1mm < 1mm; 8% of activated alumina powder with a particle size < 0.088mm; and 7% of fused magnesia powder with a particle size < 0.088mm. Pour the above materials into a forced mixer and dry mix for 2 minutes to form a dry mix. 2) Preparation of slurry: Add 6% silicon zirconium sol composite binder to the dry mixture at a rate of 0.15 kg / min and stir until the slurry is uniform; 3) Place the slurry into a mold pre-coated with a release agent and vibrate to remove air bubbles until it is compacted; 4) After demolding, bake at 108℃ and keep at this temperature for 22 hours; then heat to 1000℃ and measure the thermal conductivity at this temperature.

[0026] According to the test results, the thermal conductivity of this embodiment at 1000℃ is 0.58 W / (m・K), the flexural strength at room temperature is 10.6MPa, the compressive strength at room temperature is 82.2MPa, and the strength retention rate after 5 water cooling cycles is 89%.

[0027] Example 4 A high-strength, high-thermal-shock-stability lightweight insulating castable, comprising the following raw materials and their weight percentages: 55% of a mixture of mullite hollow spheres (0.1mm < particle size ≤ 8mm) and lightweight porous mullite clinker in any proportion, with the following particle sizes: 35% < particle size ≤ 8mm, 35% < particle size ≤ 3mm, and 30% < particle size ≤ 1mm; 24% of porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm), with the following particle sizes: 40% < particle size ≤ 3mm, and 60% < particle size ≤ 1mm; 6% of activated alumina powder (particle size < 0.088mm); 6% of fused magnesia powder (particle size < 0.088mm); and 9% of a silicon-zirconium sol-polymer composite binder, with a silicon:zirconium ratio of 1:2 and a solid content of 25%. Preparation steps: 1) Mix the following materials in any proportion: 55% hollow mullite spheres (0.1mm < particle size ≤ 8mm) and lightweight porous mullite clinker, with the following particle sizes: 35% < particle size ≤ 8mm, 35% < particle size ≤ 3mm, and 30% < particle size ≤ 1mm; 24% porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm), with the following particle sizes: 40% < particle size ≤ 3mm, and 60% < particle size ≤ 1mm; 6% activated alumina powder (particle size < 0.088mm); and 6% fused magnesia powder (particle size < 0.088mm). Pour the above materials into a forced mixer and dry mix for 2 minutes to form a dry mix. 2) Preparation of slurry: Add 9% silicon zirconium sol composite binder to the dry mixture at a rate of 0.15 kg / min and stir until the slurry is uniform; 3) Place the slurry into a mold pre-coated with a release agent and vibrate to remove air bubbles until it is compacted; 4) After demolding, bake at 112℃ and keep at this temperature for 23 hours; then heat to 1000℃ and measure the thermal conductivity at this temperature.

[0028] According to the test results, the thermal conductivity of this embodiment at 1000℃ is 0.55 W / (m・K), the flexural strength at room temperature is 10.6MPa, the compressive strength at room temperature is 82.7MPa, and the strength retention rate after 5 water cooling cycles is 88%.

[0029] Example 5 A high-strength, high-thermal-shock-stability lightweight insulating castable, comprising the following raw materials and their weight percentages: 43% mullite hollow spheres (0.1mm < particle size ≤ 8mm), with the following particle sizes: 35% for particles 3 < ≤ 8mm, 35% for particles 1 < ≤ 3mm, and 30% for particles 0.1 < ≤ 1mm; 35% porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm), with the following particle sizes: 45% for particles 1 < ≤ 3mm, and 55% for particles 0.1 < ≤ 1mm; 9% activated alumina powder (particle size < 0.088mm); 6% fused magnesia powder (particle size < 0.088mm); and 7% silicon-zirconium sol-gel composite binder (silicon:zirconium ratio 1:1, solid content 20%). Preparation steps: 1) The following materials are mixed: 43% mullite hollow spheres with a particle size of 0.1mm < ≤ 8mm, in which: 35% are 3 < 8mm, 35% are 1 < 3mm, and 30% are 0.1 < 1mm; 35% porous calcium hexaaluminate with a particle size of 0.1mm < 3mm, in which: 45% are 1 < 3mm, and 55% are 0.1 < 1mm; 9% activated alumina powder with a particle size < 0.088mm; and 6% fused magnesia powder with a particle size < 0.088mm. The mixture is then poured into a forced mixer and dry-mixed for 3 minutes to form a dry mix. 2) Preparation of slurry: Add 7% silicon zirconium sol composite binder to the dry mixture at a rate of 0.15 kg / min and stir until the slurry is uniform; 3) Place the slurry into a mold pre-coated with a release agent and vibrate to remove air bubbles until it is compacted; 4) After demolding, bake at 110℃ and keep at this temperature for 24 hours; then heat to 1000℃ and measure the thermal conductivity at this temperature.

[0030] According to the test results, the thermal conductivity of this embodiment at 1000℃ is 0.57 W / (m・K), the flexural strength at room temperature is 10.2MPa, the compressive strength at room temperature is 86.9MPa, and the strength retention rate after 5 water cooling cycles is 87%.

[0031] Example 6 A high-strength, high-thermal-shock-stability lightweight insulating castable, comprising the following raw materials and their weight percentages: 60% mullite hollow spheres (0.1mm < particle size ≤ 8mm), with the following particle sizes: 35% (3 < particle size ≤ 8mm), 35% (1 < particle size ≤ 3mm), and 30% (0.1 < particle size ≤ 1mm); 17% porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm), with the following particle sizes: 45% (1 < particle size ≤ 3mm), and 55% (0.1 < particle size ≤ 1mm); 7% activated alumina powder (particle size < 0.088mm); 8% fused magnesia powder (particle size < 0.088mm); 0.08% polypropylene fiber; and 7.92% silicon-zirconium sol-polymer composite binder (silicon:zirconium ratio 1:3, solid content 19%). Preparation steps: 1) The following materials are mixed: 60% mullite hollow spheres (0.1mm < particle size ≤ 8mm), in which: 35% are 3 < particle size ≤ 8mm, 35% are 1 < particle size ≤ 3mm, and 30% are 0.1 < particle size ≤ 1mm; 17% porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm), in which: 45% are 1 < particle size ≤ 3mm, and 55% are 0.1 < particle size ≤ 1mm; 7% activated alumina powder (particle size < 0.088mm); 8% fused magnesia powder (particle size < 0.088mm); 0.08% polypropylene fiber; 0.08% polypropylene fiber; Pour the above materials into a forced mixer and dry mix for 3 minutes to form a dry mixture; 2) Preparation of slurry: Add 7.92% silicon zirconium sol composite binder to the dry mixture at a rate of 0.15 kg / min and stir until the slurry is uniform; 3) Place the slurry into a mold pre-coated with a release agent and vibrate to remove air bubbles until it is compacted; 4) After demolding, bake at 110℃ and keep at this temperature for 24 hours; then heat to 1000℃ and measure the thermal conductivity at this temperature.

[0032] According to the test results, the thermal conductivity of this embodiment at 1000℃ is 0.54 W / (m・K), the flexural strength at room temperature is 10.7MPa, the compressive strength at room temperature is 88.4MPa, and the strength retention rate after 5 water cooling cycles is 90%.

[0033] This specific embodiment is merely a best example and is not intended to limit the implementation of the technical solution of the present invention.

Claims

1. A high-strength, high-thermal-shock-stability lightweight insulating castable, comprising the following raw material composition and weight percentage: 40-75% of mullite hollow spheres (0.1mm < particle size ≤ 8mm), or lightweight porous mullite clinker with the same particle size as the mullite hollow spheres, or a mixture of the two in any proportion; 15-40% of porous calcium hexaaluminate (0.1mm < particle size ≤ 3mm); 5-10% of activated alumina (<0.088mm particle size); 5-10% of fused magnesia (<0.088mm particle size); and 6-10% of a silicon-zirconium sol-gel composite binder.

2. The high-strength, high-thermal-shock-stability lightweight insulating castable as described in claim 1, characterized in that: Add 0.01% to 0.15% by weight of explosion-proof organic fiber.

3. The high-strength, high-thermal-shock-stability lightweight insulating castable as described in claim 2, characterized in that: The explosion-proof organic fiber refers to a composite of one or two of polypropylene fiber or polyethylene fiber.

4. The high-strength, high-thermal-shock-stability lightweight insulating castable as described in claim 1, characterized in that: In the mullite hollow spheres or lightweight mullite porous clinker with a particle size of 0.1mm < ≤ 8mm, the percentage of each particle size grade in the total weight of the added material is as follows: 3mm < ≤ 8mm accounts for 30~50%, 1mm < ≤ 3mm accounts for 20~40%, and 0.1mm < ≤ 1mm accounts for 30~50%.

5. The high-strength, high-thermal-shock-stability lightweight insulating castable as described in claim 1, characterized in that: In the porous calcium hexaaluminate with particle size of 0.1 mm < ≤ 3 mm, the percentage of each particle size grade in the total weight of the porous calcium hexaaluminate is as follows: 1 < particle size ≤ 3 mm accounts for 40~60%, and 0.1 < particle size ≤ 1 mm accounts for 40~60%.

6. The high-strength, high-thermal-shock-stability lightweight insulating castable as described in claim 1, characterized in that: The silicon-zirconium sol composite binder is composed of tetraethyl orthosilicate, ethanol, deionized water, hydrochloric acid, zirconium oxychloride, nitric acid, and γ-aminopropyltriethoxysilane. It is prepared by a series of steps including the preparation of a silica sol precursor and a zirconium sol precursor, followed by the dropwise addition of the silica sol precursor and the zirconium sol precursor. Its pH is between 2.0 and 4.

0. The solid content in the silicon-zirconium sol composite binder is 15% to 25%. The Si:Zr ratio is 1:1 to 3 or 1 to 3:

1. Its color is a pale blue emulsion.

7. A method for preparing a high-strength, high-thermal-shock-stability lightweight insulating castable as described in claim 1, comprising the following steps: 1) Preparation of dry mix: According to the particle size distribution, first add the set amount of mullite hollow spheres, or lightweight mullite porous clinker with the same particle size as mullite hollow spheres, or a mixture of the two in any proportion, porous calcium hexaaluminate, activated alumina, and fused magnesia, and pour the materials into a forced mixer and dry mix for 1 to 3 minutes to form a dry mix; when explosion-proof organic fibers are added, they are also poured in and mixed together. 2) Preparation of slurry: Add the set amount of silicon-zirconium sol composite binder to the dry mixture at a rate of 0.1-0.5 kg / min, and then stir until the slurry is uniform; 3) Place the slurry into a mold pre-coated with a release agent and vibrate to remove air bubbles until it is compacted; 4) After demolding, bake at 105-115℃ and keep warm at this temperature for no less than 20 hours; When it is necessary to measure the thermal conductivity, heat treatment is performed after baking, with the temperature heated to no higher than 1100℃, and the thermal conductivity is measured at this temperature.